The Urgency of Integrating Local Wisdom and Disaster-Resilient Character in the Merdeka Curriculum through the Disaster-Safe Education Unit - Susilawati, Susilawati; Sofyan, Hizir; Ilhamsyah, Yopi; Ridha, Syahrul (Geosfera Indonesia, 2024)
Disasters can occur at unpredictable times; therefore, an appropriate disaster mitigation is needed. This research question is about how to integrate local wisdom and disaster resilience in the Merdeka Curriculum through a disaster-safe education program unit. Therefore, this study aims to reveal the importance of this integration. Questionnaires were distributed via Google Forms to all teachers in Aceh and several other regions in Indonesia, such as vocational school teachers in Kalimantan. A total of 144 teachers were respondents in this research. In addition, data was collected through the study literature review (SLR) method. The results of this study are (1) the value of local wisdom needs to be integrated into learning in the Merdeka curriculum to improve disaster resilience, (2) the Project Strengthening Pancasila Profile in the Merdeka Curriculum can support the integration of local cultural values and the character of disaster resilience, (3) the program The Disaster Safe Education Unit has an important role in disaster risk reduction. Therefore, stakeholders, the community, and the government need to pay attention to this condition to create students and communities who have a disaster-resilient character.